A board game as educational tool to teach pharmacology for pharmacy students (Research, Society and Development, 2022)
Games have a considerable motivational capability, usually bringing a series of mechanisms (score levels, awards, competitiveness, enjoyment) to encourage people. However, its effective incorporation into the educational field requires planning and pedagogical integration. Following behaviorism and gamification theoretical bases for active learning, a board game focused on pharmacology was created. Corew Drawn X7 software was utilized to develop the board. Microsoft Word was utilized to elaborate the cards. Concerning data extraction for incorporation into the board and cards, Medscape and Uptodate were utilized to collect relevant scientific information. A 30-question test on several pharmacology topics was applied before and after educational activity. Ongoing with this methodological idea, a feedback pool was applied to the participants after activity. 60 pharmacy students, enrolled in the pharmacology course, participated of this board game. After pretest and posttest application among players, data shows that posttest scores were significantly higher. The students have shown a likely acceptance for prospective gamification activities within the academic field. Moreover, this gamified instructional material has potential to help student’s academic background, especially within the field of pharmacology.